Pengendalian Limpasan Pada Lahan Miring Menggunakan Metode Ekodrainase - Awaluddin; Rahmawati; Didi, Andi Bustan (Fakultas Teknik Universitas Muhammadiyah Parepare, 2024)
The drainage concept common mistake that often occurs is dumping stagnant water into the river which will exceed the river's capacity, resulting in flooding. The eco drainage system can be a more environmentally friendly solution by absorbing as much surface runoff as possible into the soil naturally or channeling the water into rivers without exceeding the river's capacity limits. This research aims to determine how much water runoff is on sloping land, the effectiveness of the eco drainage method in controlling water runoff and its effect in increasing soil infiltration on sloping land. This experimental research was tested using a Rainfall Simulator with slopes of 13° and 20° and dead-end drainage holes. On a land slope of 13⁰ with rainfall of 3.67 L/minute, the amount of runoff with dead-end drainage is 3.71 L/minute and without which is 4.14 L/minute. Meanwhile on a land slope of 20⁰ with rainfall of 3.99 L/minute, the amount of runoff with dead-end drainage is 8.4 L/minute and without which is 9,63 L/minute. Providing dead-end drainage on sloping land can reduce the speed of surface runoff which will then enter the soil in the form of infiltration water.